On the Number of Limit Cycles in a Liénard-Like Perturbation of a Non-linear Quadratic Isochronous Center - Ellaggoune, Selma; Fernane, Khaireddine (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper we estimate the maximum number of limit cycles that can bifurcate from an integrable non-linear quadratic ischronous center, when perturbed inside a class of Liénard-like polynomial differential systems of arbitrary degree $n$. The main tool employed in this study is the averaging theory of first order.